The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4269/ajtmh.21-1222
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Flubendazole as an Anthelmintic Treatment for Guinea Worm (Dracunculus medinensis): Clinical Trials in Laboratory-Reared Ferrets and Domestic Dogs in Chad

Abstract: Dracunculus medinensis (Guinea worm [GW]), a zoonotic nematode targeted for eradication, has been managed using interventions aimed at humans; however, increases in domestic dog GW infections highlight the need for novel approaches. We conducted two clinical trials evaluating the efficacy of subcutaneously injected flubendazole (FBZ) as a treatment of GW infection. The first trial was conducted administering FBZ to experimentally infected ferrets; the second trial involved administering FBZ or a placebo to dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A small number of the dogs sampled in this study (n = 13) were positive for B. c. [21,37,38]. The lack of B. c. rossi in our dogs may be due to the low number (n = 14) of dogs infested with Haemaphysalis leachii [11]. Additional studies to determine the distribution and factors related to the presence and intensity of H. leachii are needed to better understand the risk of severe babesiosis to the health of dogs in Chad.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A small number of the dogs sampled in this study (n = 13) were positive for B. c. [21,37,38]. The lack of B. c. rossi in our dogs may be due to the low number (n = 14) of dogs infested with Haemaphysalis leachii [11]. Additional studies to determine the distribution and factors related to the presence and intensity of H. leachii are needed to better understand the risk of severe babesiosis to the health of dogs in Chad.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, there are few data on tick-borne pathogens in domestic dogs in Chad. Previous studies by our group on domestic Chadian dogs revealed high rates of tick infestation [11], a lack of heartworm (Diro laria immitis) infections, and infections with a Brugia sp. that was previously unreported in dogs in Central Africa [12].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is routinely used in veterinary medicine for the treatment of selected parasites, primarily gastrointestinal nematodes of poultry and livestock [1]. There is also growing interest in using this drug to treat or prevent filarial infections [1,2]. The mode of action for flubendazole is based on binding to tubulin, with a preferential binding to nematode tubulin compared to mammalian tubulin [3].…”
Section: Flubendazolementioning
confidence: 99%